Stifnerli Gemi Panellerinin Nihai Mukavemetinin Tayini - Özdemir, Murat; Ergin, Ahmet (Teorik ve Uygulamalı Mekanik Türk Milli Komitesi, 2015)
Elastic-plastic large deflection FEM calculations are performed to examine the collapse behaviour of stiffened panels. In the present study, panels with small size stiffeners are focused on. Furthermore, ultimate strength of stiffened panels is estimated by a simplified method, so called FY Method, considering different buckling strength formulas for stiffened panels. Candidate buckling strength formulas are assessed, then a new overall buckling strength formula is proposed by the authors. Finally, possible reasons of difference between estimated results are discussed.

Stifnerli gemi panellerinin göçme davranışını incelemek amacıyla doğrusal olmayan sonlu elemanlar analizleri gerçekleştirilmiştir. Bu çalışma kapsamında genel burkulma ve göçmeye maruz kalan küçük boyutlu stifnerlerle desteklenmiş paneller incelenmiştir. Ayrıca panellerin nihai mukavemet değerleri yaklaşık bir yöntem ile tayin edilmiştir. Nihai mukavemetin tayini amacıyla farklı genel burkulma formülleri incelenmiş ve yeni bir yaklaşım geliştirilmiştir. Son olarak sonuçlar arasındaki farkların muhtemel sebepleri irdelenmiştir.

Conference Paper -- Theoretical and Applied Mechanical Turkish National Committee, 2015

Konferans Bildirisi -- Teorik ve Uygulamalı Mekanik Türk Milli Komitesi, 2015